2022
DOI: 10.3390/app12073252
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Profiles of Recreational Runners and Cyclists Aged 20 to 60 Years

Abstract: Human physical activities may bring potential health benefits. The aim of our study was to compare body composition, lung function and aerobic fitness as a function of age in a cross-sectional study of 277 recreational cyclists (men: n = 163, women: n = 114) and 377 recreational runners (men: n = 239, women: n = 138) aged 20 to 60 years, with a training volume of about 2000 to 4000 km per year for cyclists and 25 to 60 km per week for runners. The survey focused on comparing the values of body composition, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Similarly, group-level work indicates that physical activity has associations with multiple factors, including, e.g., diet [78], gut microbiome [79], emotion regulation [80], fitness [81], weather [82], and metabolic [83] factors. Adding to group-level findings, studies using micro-longitudinal tracking and within-individual analyses have shown physical activity's associations with, e.g., sleep [84][85][86][87] and stress [88].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, group-level work indicates that physical activity has associations with multiple factors, including, e.g., diet [78], gut microbiome [79], emotion regulation [80], fitness [81], weather [82], and metabolic [83] factors. Adding to group-level findings, studies using micro-longitudinal tracking and within-individual analyses have shown physical activity's associations with, e.g., sleep [84][85][86][87] and stress [88].…”
Section: Discussionmentioning
confidence: 99%